Pengaruh Kinerja Keuangan dan Makroekonomi terhadap Pembiayaan Jual Beli dan Pembiayaan Bagi Hasil di KB Bank Syariah Periode 2015.1-2025.2 - Zakiyatul Maulidiyah; Fira Nurafini (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The development of financing in Islamic Commercial Banks in Indonesia has shown an increasing trend in recent years, both in sales and purchase financing and profit-sharing financing. However, this growth is inseparable from the dynamics of internal bank factors and macroeconomic conditions that affect the stability of financing distribution. This study aims to analyze the influence of bank financial performance as proxied by the Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), Return on Assets (ROA), Operating Expenses to Operating Income (BOPO), and Financing to Deposit Ratio (FDR), as well as macroeconomic factors consisting of Inflation, Economic Growth, and the BI Rate on sales and purchase financing and profit sharing financing in Islamic Commercial Banks for the period 2015.1–2025.2. This study uses a quantitative approach with secondary data in the form of 42 quarterly observations and analyzed using the VAR/VECM method. The results show that in the long term the variables CAR, NPF, ROA, BOPO, FDR, inflation, economic growth, and the BI Rate have a significant influence on sales and purchase financing and profit-sharing financing. Meanwhile, in the short term, all of these variables do not show a significant influence on both types of financing.